SOUND GRAMMAR, FLAWED REASONING: RHETORICAL FALLACIES IN ARGUMENTATIVE WRITING OF ENGLISH EDUCATION THESES - Stevani, Margaret; Alexander Adrian Saragi; Happy Kusuma Wardani (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
This study investigated the prevalence and types of rhetorical fallacies in the argumentative sections of English education theses, despite overall grammatical accuracy. Drawing on Toulmin’s argument model, cognitive reasoning theories, and nexus-juncture analysis, three-fifty undergraduate theses from three universities in Indonesia were analyzed qualitatively. Common fallacies such as hasty generalization, false cause, strawman, circular reasoning, and either/or reasoning were identified and mapped onto Toulmin’s components (claims, warrants, backing, rebuttals). Findings revealed that students demonstrated competency in grammatical structures but often lacked logical consistency in their arguments which led to flawed reasoning that undermined their thesis statements. The findings recommended that integrating rhetorical fallacy identification into writing instruction could improve both the clarity and validity of student arguments. This study highlighted the need for focused pedagogical strategies to address both grammar and reasoning skills in argumentative writing to promote effective and persuasive academic communication in English education.